Basal Encephalocele Presenting with Bitemporal Hemianopsia in an Adult Male. (4th May 2018) - Moore, Tyler; Freedman, Kenn
ABSTRACT: Basal encephaloceles are uncommon malformations that are usually congenital in nature, although, occasionally, they can be traumatic. When they are congenital, they are associated with skull and facial midline defects, central nervous system abnormalities, and possible ocular and visual problems. The authors present a case of an adult male with a basal encephalocele who presented with a bitemporal hemianopsia. Ocular abnormalities, visual loss, and visual field deficits have previously been reported in patients with basal encephalocele; however, there does not appear to be any reported cases with formal visual field testing to demonstrate specific defects such as a bitemporal hemianopsia.